Convert! : designing Web sites to increase traffic and conversion - Hunt, Ben (Ben R.) (Indianapolis, Ind. : Wiley Pub., 2011)
Provides advice on Web site design and Internet marketing to increase traffic and improve the site's conversion rate.
pt. 1. Designing for traffic -- pt. 2. Designing for conversion.
Includes index.
Print version record.
Keywords: Web sites -- Design; Web sites -- Marketing; Internet marketing; Internet advertising; Electronic commerce; Electronic commerce; Internet advertising; Internet marketing; Web sites -- Design; Web sites -- Marketing; Web sites -- Design; Web sites -- Evaluation; Web sites -- Testing; Electronic books; Electronic books